2015
DOI: 10.1039/c4pp00368c
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo evaluation of photodynamic inactivation using Photodithazine® against Candida albicans

Abstract: This study describes the photoinactivation of Candida albicans in a murine model of oral candidosis, mediated by Photodithazine® (PDZ). Six-week-old female Swiss mice were immunosuppressed, and inoculated with C. albicans to induce oral candidosis. After five days, photodynamic inactivation (PDI) mediated by PDZ at concentrations of 75, 100, 125 and 150 mg L(-1) was applied on the tongue of mice. Next, microbiological evaluation was performed by recovering C. albicans from the tongue via colony forming units (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 32 publications
0
36
0
1
Order By: Relevance
“…Indeed, the divergences of the outcomes should be carefully analyzed. In this in vivo study, the PS was applied directly on the mouse tongue cells [104] and the cells permeability associated with the physiological environment might have increased the PS absorption, which is in contrast to previous study [21]. A sequence of in situ studies [95,103,105] have shown high effect of aPDT with chlorine e6 (Ce6) against initial and mature oral biofilm reducing significantly the numbers of viable anaerobic microorganisms.…”
Section: Apdt -Definition Application and Mechanism Of Actionmentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, the divergences of the outcomes should be carefully analyzed. In this in vivo study, the PS was applied directly on the mouse tongue cells [104] and the cells permeability associated with the physiological environment might have increased the PS absorption, which is in contrast to previous study [21]. A sequence of in situ studies [95,103,105] have shown high effect of aPDT with chlorine e6 (Ce6) against initial and mature oral biofilm reducing significantly the numbers of viable anaerobic microorganisms.…”
Section: Apdt -Definition Application and Mechanism Of Actionmentioning
confidence: 90%
“…Quite divergent results were found in recent and interesting investigations [95,[103][104][105]. A recent study showed the antimicrobial effect of aPDT associated to PDZ with 4.36 log 10 of C. albicans reduction when the experiment was performed in animals [104]. Indeed, the divergences of the outcomes should be carefully analyzed.…”
Section: Apdt -Definition Application and Mechanism Of Actionmentioning
confidence: 96%
See 1 more Smart Citation
“…Depending on a proper delay time between drug administration and irradiation (incubation time), the PS can be more concentrated in the microorganism when compared to the host cells, resulting in a higher PDI response. Recent studies show the effect of various PS against C. albicans , such as a chlorine derivate (Photoditazine) , methylene blue , curcumin , hematoporphyrin derivate (Photogem) , and cationic porphyrins .…”
Section: Introductionmentioning
confidence: 99%
“…To induce candidiasis in the animals, we used the method previously described (Takakura et al, 2003) and reproduced by our group (Mima et al, 2010;Dovigo et al, 2013;Carmello et al, 2015). During the experimental period, the animals were treated with tetracycline 0.83 mg ml À1 (Santa Paula Pharmacy, Araraquara, SP, Brazil) administered through the drinking water.…”
Section: Induction Of Oral Candidiasis and Treatmentsmentioning
confidence: 99%